Radar interferometric monitoring unique buildings in Astana - Aitkozhin, Азамат (Рroblems of engineering and professional education, 2023)
As is known, based on the results of multipass space radar surveys of the same territory, performed with the same parameters and survey geometry, it is possible to estimate the displacements of the earth's surface or buildings and structures with a centimeter (for the earth's surface) and even millimeter (for buildings and structures). To solve this problem it is necessary to perform interferometric processing of radar images of the multipass series.